Corak Tafsir Naqli Ibnu Katsir dalam Surat Al-Baqarah ayat 172 - Fajir, Nurul (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This study aims to analyze the interpretive method used by Ibn Kathir in explaining Surah Al-Baqarah verse 172, which discusses the command to consume good (halal) sustenance and the importance of gratitude to Allah SWT. The interpretive method used by Ibn Kathir in his work, Tafsir Al-Qur'an al-Azim, is known as tafsir bi al-ma'tsur, which emphasizes the use of authentic narrations from the Qur'an, hadith, and the opinions of the companions and tabi'in (successors). This study employs a qualitative approach with a literature review method to trace Ibn Kathir's interpretive sources and compare them with other exegeses to gain a deeper understanding. The analysis shows that Ibn Kathir integrates the interpretation of Qur'anic verses with textual and historical approaches, utilizing hadith narrations and asbab al-nuzul (circumstances of revelation) to explain the context of the verse. Furthermore, Ibn Kathir links the meaning of the verse with the principles of Islamic law concerning halal and haram food, as well as its spiritual implications, namely gratitude as an essential form of worship. This approach provides a comprehensive and in-depth view of how Islamic values are applied in the daily life of Muslims.The study concludes that Ibn Kathir's interpretive method offers a clear and authoritative guide to understanding the content of the Qur'an, particularly in relation to the aspects of Sharia and aqidah in Surah Al-Baqarah verse 172. This analysis also affirms the relevance of Ibn Kathir's exegesis in the development of contemporary Qur'anic studies and its contribution to building a holistic understanding of Islamic teachings.